Enhanced Susceptibility to Chemoconvulsant-Induced Seizures in Ganglioside GM3 Synthase Knockout Mice. (July 2020) - Tang, Fu-Lei; Wang, Jing; Itokazu, Yukata; Yu, Robert K.
Ganglioside GM3 synthase (α-2, 3-sialyltransferase, ST3GAL5, GM3S) is a key enzyme involved in the biosynthesis of gangliosides. ST3GAL5 deficiency causes an absence of GM3 and all downstream biosynthetic derivatives. The affected individuals manifest deafness, severe irritability, intractable seizures, and profound intellectual disability. To investigate whether deficiency of GM3 is involved in seizure susceptibility, we induced seizures with different chemoconvulsants in ST3GAL5 knockout mice. We report here that ST3GAL5 knockout mice are hyperactive and more susceptible to seizures induced by chemoconvulsants, including kainate and pilocarpine, compared with normal controls. In the hippocampal dentate gyrus, loss of GM3 aggravates seizure-induced aberrant neurogenesis. These data indicate that GM3 and gangliosides derived from GM3 may serve as important regulators of epilepsy and may play an important role in aberrant neurogenesis associated with seizures.